The acute effects of high-intensity jack-knife stretching on the flexibility of the hamstrings - Kosuke Takeuchi (Nature Portfolio, 2021)
Abstract The purpose of the present study was to examine the acute effects of high-intensity jack-knife stretching for 60 s on flexibility of the hamstrings. Twelve healthy participants underwent jack-knife stretching for 60 s (3 repetitions of 20 s stretching with 30 s intervals) at two different intensities based on the point of discomfort (POD and PODmax). To examine any change in flexibility, knee extension range of motion (ROM), passive torque at end ROM, and muscle–tendon unit stiffness were measured before and after stretching. To evaluate hamstrings pain, a numerical rating scale (NRS) was described. The knee extension ROM (p < 0.01) and passive torque at end ROM (p < 0.05) were significantly increased at both intensities. The muscle–tendon unit stiffness was significantly decreased in PODmax intensity (p < 0.01), but there was no change in POD intensity (p = 0.18). The median values of NRS during the stretching were 0 and 6–7 in POD and PODmax intensity, respectively, although it was 0 immediately after the stretching protocol in both intensities. These data suggested that high-intensity jack-knife stretching is an effective and safe method to decrease muscle–tendon unit stiffness of the hamstrings.